2017
DOI: 10.1101/202101
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-invasive imaging reveals conditions that impact distribution and persistence of cells after in vivo administration

Abstract: BackgroundCell-based regenerative medicine therapies are now frequently tested in clinical trials. In many conditions, cell therapies are administered systemically, but there is little understanding of their fate, and adverse events are often under-reported. Currently, it is only possible to assess safety and fate of cell therapies in preclinical studies, specifically by monitoring animals longitudinally using multimodal imaging approaches. Here, using a suite of in vivo imaging modalities to explore the fate … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 56 publications
3
44
0
Order By: Relevance
“…11 On culling the mice, no tumor was detected in the major body organs (liver, spleen, brain, heart, and lungs). A key objective of this study was to investigate what happened to the free and encapsulated SPIONs after day 1 when BLI showed that the majority of the cells had died.…”
Section: Animal Injection and In Vivo Monitoring Of The Bio-distributmentioning
confidence: 99%
See 4 more Smart Citations
“…11 On culling the mice, no tumor was detected in the major body organs (liver, spleen, brain, heart, and lungs). A key objective of this study was to investigate what happened to the free and encapsulated SPIONs after day 1 when BLI showed that the majority of the cells had died.…”
Section: Animal Injection and In Vivo Monitoring Of The Bio-distributmentioning
confidence: 99%
“…11 Here, MRI allowed the monitoring of in vivo clearing and accumulation pattern of particles ( was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity.…”
Section: Mri Complementary To Blimentioning
confidence: 99%
See 3 more Smart Citations